A Study of CSR in the Software Industry in India - Gupta, Vidhi (2007)
Corporate Social Responsibility is the degree of moral obligation that may be ascribed to corporations beyond simple obedience to the laws of the state. The idea that a corporation can operate free of any moral restraints is absurd. (Kilcullen and Kooistra, 1999)The primary objective of this dissertation is to examine the status quo of CSR in the IT industry in India and recognize the gaps between theoretical underpinnings and tangible integration of industry level CSR in India. A preliminary look at the data available through several sources suggests that CSR in Indian industries is somewhat ambiguous and is limited to the social development of the country, given its strong embeddings in philanthropy and community participation. The IT industry being a global one needs to be more proactive in deploying CSR towards the management of its other stakeholders such as employees, governments, clients, environment, etc in order to attain a competitive advantage in the marketplace.